1 - Introduction - Murunga, Godwin R.; Diagne, Souleymane Bachir (Africa Development, 2009)
This introductory article explains the origins of this special issue initiative in the work of a select number of African graduate students in the US. It locates the different articles included in the volume in the general framework of debates about the imbalances in knowledge production on Africa between the global North and South. It highlights the issue of the role which the fourth generation of African scholars is to play in these politics. It concludes by summarising the contributions to this topic of the various articles included in this special issue.